MRI of pancreatic neuroendocrine tumours. - Owen, N; Sohaib, SA; Peppercorn, P; Monson, J; Grossman, AB; Besser, G; Reznek, R (2001)
Neuroendocrine tumours of the pancreas are rare and are frequently difficult to demonstrate. Several imaging modalities have been used to demonstrate these tumours, but recent reports have suggested that MRI may have an important role in their localization. We review the spectrum of MRI appearances of pancreatic neuroendocrine tumours.